Socio-regional speech versus "Oxford accent" - trends and fashions in the pronunciation of English English - Wotschke, Ingrid (HERMES - Journal of Language and Communication in Business, 2017)
Post-War years have brought new speech habits and evaluations on grounds of so far unprecedented social contacts between the classes. The following paper will focus on recent articulatory developments together with their socio-economic roots and psy-chological implications, to assess the effects of cross-cultural influence on educated Southern British English.